Influence of BAZ on fasting blood glucose levels as a prediabetes indicator in adolescents in Jambi City - Egy Sunanda Putra; Junita Junita; Sarinah Siregar (Department of Nutrition at the Health Polytechnic of Aceh, Ministry of Health, 2024)
Prediabetes is an intermediate stage of impaired glucose tolerance (IGT). If left unresolved for 3-5 years, it can significantly increase the risk of developing diabetes mellitus. Body mass index (BMI) for age score (BAZ) is a key indicator of lifestyle choices that influence the risk of prediabetes. Objective: To investigate the interaction between BAZ and fasting blood glucose as a prediabetes indicator. The methods. This cross-sectional study was conducted at Senior High School 2 in Jambi City in 2019. A total of 140 participants aged 15-18 years were included, meeting criteria such as parental/guardian consent, willingness to participate, and fasting from 11 p.m. to 7:30 a.m. Independent variables included a family history of diabetes mellitus, family history of obesity, consumption of carbohydrates, fats, sugary drinks, waist-to-height ratio, physical activity, and BMI. The dependent variable, prediabetes, was measured using fasting blood glucose with a spectrophotometer biochemical analyzer AE-600N at a wavelength of 500 nm. Data were analyzed using the chi-squared test and multiple logistic regression analysis, The results showed a significant interaction between BMI and prediabetes (p=0,026; OR=4,34) after confounding factor analysis of family history of diabetes (p=0,050; OR=3,00), physical activity (p=0,020; OR=5,012), and sugar-sweetened beverages (p=0,018; OR=4,21), even after adjusting for other independent variables. In conclusion, BAZ > 1 SD was the dominant factor associated with an increased risk of prediabetes.